AB0568 Giant Cell Arteritis and Malignancy – More than Just A Coincidence?. (15th July 2016) - Ješe, R.; Hočevar, A.; Rotar, Ž.; Praprotnik, S.; Tomšič, M.
Abstract : Background: Malignancy associated vasculitis represents 2–5% of systemic vasculitides. While there have been reports of increased incidence of malignancy in patients with giant cell arteritis (GCA) no definite association has yet been established. Objectives: To determine the proportion patients with GCA and past/concurrent/subsequent malignancy. Methods: We conducted a prospective longitudinal analysis of patients diagnosed with GCA from September 2011 to December 2015 at a single secondary/tertiary rheumatology centre. The proportion of patients with past, concurrent, and successive malignancy (diagnosed within 1 year of follow-up) was determined. Crude incidence rate (CIR) of malignancy in general population aged 50 years and above from the same geographical region in year 2011 and 2012 (final accessible reports based on complete yearly data) was acquired from Slovenian Cancer Registry for comparison. Results: During the observation period 106 new GCA cases were identified (Table 1 ). Nineteen patients (17.9%) were diagnosed with a malignancy at any point in time (Table 2 ). In 7 patients (6.6%) malignant disease was found concomitantly with GCA (4/7) or within one year of follow-up (3/7). With respect to location of these 7 newly diagnosed malignancies, there were 4 cases (3.8%) of urinary bladder cancer (Table 2 ). There was 1 death due to cancer during the follow-up. None of the 12 patients with a history of past malignant disease had a recurrence of cancer at GCA diagnosis or during the follow-up. CIR for malignancy in comparably aged population of the same geographical region was 1.51%, with cumulative CIR for urinary tract malignancy of 0.08% and specific CIR for bladder cancer of 0.04%. Conclusions: In our study, 6.6% of GCA patients were found to have a concurrent malignant disease compared to 1.5% of similarly aged general population. Additionally, we detected an increased incidence of urinary bladder cancer in our GCA cohort. Disclosure of Interest: None declared